E-didactics design of differential calculus based on TPACK to overcome learning obstacles for mathematics pre-service teachers - Meika, Ika; Sartika, Nenden Suciyati; Sujana, Asep; Jarinah, Jarinah; Hakim, Zaenal; Windiarti, Ika Safitri; Hendra, Hendra (IKIP Siliwangi and I-MES, 2025)
Many mathematics pre-service teachers face obstacles in understanding basic differential calculus concepts, which could affect their teaching abilities. A deep understanding of learning obstacles and developing relevant learning strategies is necessary to address this issue. This research aims to identify learning obstacles experienced by mathematics pre-service teachers in differential calculus and evaluate the effectiveness of an e-didactics design based on TPACK in overcoming those obstacles. The research method is Design-Based Research (DBR) with the Plomp development model, which includes the stages of analysis, design, evaluation, and revision. The subjects involve 39 mathematics pre-service teachers from Mathla’ul Anwar University and La Tanza Mashiro University, Banten, Indonesia. Research instruments include pretest, post-test, validation, and effectiveness questionnaires with data analysis covering walkthrough, documents, triangulation, instruments, and qualitative analysis. The finding identifies three types of learning obstacles: ontogenic, epistemological, and didactical. The improvement in learning outcomes demonstrates the effectiveness of the e-didactics design: 52% in real number systems and functions, 74% in limits, 88% in derivatives, and 65% in the application of derivatives. The effectiveness survey recorded a score of 83%, indicating that the e-didactics design of differential calculus based on TPACK effectively addresses learning obstacles.